Characteristics of vertical stability of the body of hard hearing primary school children during physical education - Storozhik A.І. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
Studied the specific features of the motor areas of hearing children of primary school age - the vertical stability of their body. In pedagogical experiment involved 58 hearing children of primary school age and 52 healthy student. The analysis of the amplitude-frequency characteristics of the common center of gravity of the body. Revealed a statistically significant difference in the sagittal and frontal planes between the studied parameters of the surveyed population. The data obtained can be used for quantitative assessment of the vertical stability of the body younger students. The results of the experiment can serve as a basis for the development of technology aimed at the formation of the orthograde posture younger students this nosology.